2017
DOI: 10.1007/978-3-319-47145-7_22
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable City around Indian Alpine Wetland: A Case of Mirik Lake, West Bengal

Abstract: The high-altitude lake systems of the Himalayas in Kashmir and Ladakh have unique variations in their water chemistry and fauna and flora.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Morphologically, the 3-verticillate petiolate leaves of D. phuquocensis are shared with several species of Didymocarpus , such as D. insulsus Craib (north-eastern, Thailand), D. tristis Craib (Chanthaburi Province, south-eastern Thailand), D. dongrakensis B.L.Burtt (northeast Thailand) D. newmanii B.L.Burtt (Chanthaburi Province, south-eastern Thailand), D. pulcher (from India, Buhtan, Nepal, China to Vietnam), D. hookeri (Assam, Arunachal Pradesh, Meghalaya and Sikkim, India), D. punduanus (Assam, Meghalaya and Nagaland, India) ( Wang et al 1998 ; Nangngam and Maxwell 2013 ; Phuong et al 2014 ; Sinha and Datta 2016 ; Roy 2017 ). Of these, the campanulate calyx of the new species is similar to D. pulcher , D. hookeri and D. punduanus , but distinguished from D. insulsus , D. newmanii and D. tristis which have the calyx 5-lobed to the base.…”
Section: Taxonomic Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Morphologically, the 3-verticillate petiolate leaves of D. phuquocensis are shared with several species of Didymocarpus , such as D. insulsus Craib (north-eastern, Thailand), D. tristis Craib (Chanthaburi Province, south-eastern Thailand), D. dongrakensis B.L.Burtt (northeast Thailand) D. newmanii B.L.Burtt (Chanthaburi Province, south-eastern Thailand), D. pulcher (from India, Buhtan, Nepal, China to Vietnam), D. hookeri (Assam, Arunachal Pradesh, Meghalaya and Sikkim, India), D. punduanus (Assam, Meghalaya and Nagaland, India) ( Wang et al 1998 ; Nangngam and Maxwell 2013 ; Phuong et al 2014 ; Sinha and Datta 2016 ; Roy 2017 ). Of these, the campanulate calyx of the new species is similar to D. pulcher , D. hookeri and D. punduanus , but distinguished from D. insulsus , D. newmanii and D. tristis which have the calyx 5-lobed to the base.…”
Section: Taxonomic Treatmentmentioning
confidence: 99%
“…A critical examination of living flowers, herbarium specimens of these plants and comparison with type material and protologues of all closely-related species in Vietnam and neighbouring countries (e.g. Clarke 1874 , 1883 , 1884 ; Wallich 1829 ; Wang et al 1998 ; Pham 2000 ; Nangngam and Maxwell 2013 ; Phuong et al 2014 ; Nangngam and Middleton 2014 ; Sinha and Datta 2016 ; Roy 2017 ), suggested that these specimens were different from the other known Didymocarpus species. These plants with 3-verticillate, petiolate leaves, campanulate calyx, funnelform corolla found in Phu Quoc NP show similarities in these characters with D. pulcher , D. hookeri C.B.Clarke and D. punduanus Wall.…”
Section: Introductionmentioning
confidence: 98%